The Effect of Weather and Location of Fruit within the Tree on the Incidence and Severity of Citrus Black Spot on Fruit - Hendricks, Katherine E. (Sci Rep, 2020)
Citrus black spot (CBS) caused by the fungus Phyllosticta citricarpa occurs in tropical and sub-tropical citrus production regions and affects all varieties of citrus. In Florida, the disease cycle is unique, having only the asexual spore. This work examines incidence and severity of CBS (hard spot symptoms) on fruit in two citrus groves during 2013–2014, 2014–2015 (Grove III) and 2015–2016 (Grove II) citrus seasons. Disease incidence and severity on fruit were analyzed based on citrus season, side of tree evaluated, height within the canopy, tree health, and tree age. Results indicate an increase in CBS incidence in Grove III between 2013–2014 and 2014–2015 seasons, with more infected or symptomatic fruit on the road side of the canopy and a higher incidence above 2 meters. Tree health status affected incidence but not severity and tree age had a significant effect on severity of CBS in Grove II. Analysis of weather data conducive for infection, between 2010 and 2017, indicated an average of 172 days per year (range: 104–261 days) when the temperature (15–35 °C) and relative humidity (RH ≥ 90% for 8 consecutive hours) were conducive for infection of fruit and an average of 98 days per year (range: 72–123 days) when the fruit were susceptible to infection.